A Universal art : Hebrew grammar across disciplines and faiths - Vidro, Nadia; Zwiep, Irene E., 1962-; Olszowy-Schlanger, Judith (Studies in Jewish history and culture ;, 2014)
This book reflects on medieval and early modern Hebrew linguistics as a discipline that crossed geographic and religious borders and linked up with a plethora of scholarly activities, from Judaeo-Arabic Bible translations to the Renaissance search for the holiest alphabet. This collection of articles presents a cross-section of new research avenues on Hebraism, Karaite, Rabbanite and Christian, with an emphasis on the transmission of linguistic ideas through time and space among different communities, cultures and religious currents. The resulting picture is one of intrinsic variation and dynamic growth as opposed to the linear paradigm of development, culmination and stagnation current in the historiography of Hebrew linguistics.